Comparative analysis of basal lamina type IV collagen alpha chains, matrix metalloproteinases-2 and-9 expressions in oral dysplasia and invasive carcinoma - Tamamura, R.; Nagatsuka, H.; Siar, C.H.; Katase, N.; Naito, I.; Sado, Y.; Nagai, N. (2013)
The aim of this study was to compare the expressions of basal lamina (BL) collagen IV alpha chains and matrix metalloproteinases (MMP)-2 and MMP-9 in oral dysplasia (OED) and invasive carcinoma. Ten cases each of OEDs, carcinomas-in situ and oral squamous cell carcinomas (OSCCs) were examined by immunohistochemistry. Another 5 cases, each of normal and hyperplastic oral mucosa, served as controls. Results showed that alpha 1(IV)/alpha 2(IV) and alpha 5(IV)/alpha 6(IV) chains were intact in BLs of control and OEDs. In BLs of carcinoma-in situ, alpha 1(IV)/alpha 2(IV) chains preceded alpha 5(IV)/alpha 6(IV) chains in showing incipient signs of disruption. OSCCs exhibited varying degrees of collagen alpha(IV) chain degradation. MMP-2 and MMP-9 were absent in controls and OED, but weakly detectable in carcinoma-in situ. In OSCC, these proteolytic enzymes were expressed in areas corresponding to collagen alpha(IV) chain loss. Enzymatic activity was enhanced in higher grade OSCC, and along the tumor advancing front. Overall the present findings suggest that loss of BL collagen alpha(IV) chains coincided with gain of expression for MMP-2 and MMP-9, and that these protein alterations are crucial events during progression from OED to OSCC. (C) 2012 Elsevier GmbH. All rights reserved.